PEMBUATAN PETA SITUASI DUSUN BABADAN, DESA BELUK KECAMATAN BAYAT, KABUPATEN KLATEN - , INTAN PRATAMA BAYU A ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The Final report titled \"SITUATION MAP PRODUCTION OF BABADAN HAMLET BELUK VILLAGE BAYAT SUB DISTRICT KLATEN DISTRICT CENTRAL JAVA PROVINCE\" describes the measurement and mapping of terrestrial to obtain spatial data. Spatial data in the form of planimetric detail and high detail then presented in the form of a map. The result is a situation map scale 1: 500 BABADAN HAMLET BELUK VILLAGE BAYAT SUB DISTRICT KLATEN DISTRICT CENTRAL JAVA PROVINCE. Map this situation using WGS'84 datum (World Geodetic System) and projection UTM (Universal Trasverse Mercator).